1988
DOI: 10.1152/ajpregu.1988.254.2.r170
|View full text |Cite
|
Sign up to set email alerts
|

Fasting in king penguin. I. Hormonal and metabolic changes during breeding

Abstract: During long-term fasting in birds and mammals, protein utilization initially decreases (phase I), is thereafter maintained at a low value (phase II), and then further increases (phase III). To delineate hormonal and biochemical changes responsible for these modifications, the effect of food deprivation for 50 days was studied in 6 male king penguins captured at the beginning of their natural breeding fast. During phase II, both rate of mass loss and plasma uric acid concentration remained at low levels, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
184
5

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(199 citation statements)
references
References 33 publications
10
184
5
Order By: Relevance
“…Likewise, we did not find a direct relationship between body mass and prolactin levels in incubating female eiders, because the birds seldom reach a phase III during normal incubation (Criscuolo et al, 2001). Such a result is consistent with the incubation strategy of capital incubators, which because they depend almost exclusively on their endogenous nutrient reserves are able to lose a large amount of body mass without threatening their reproduction or survival (Cherel et al, 1988;Moreno, 1989). On the other hand, a deteriorated adult body condition at hatching could have an impact on the posthatch parental behavior.…”
Section: Mass Loss Prolactin Levels At Hatching and Posthatch Parensupporting
confidence: 81%
See 1 more Smart Citation
“…Likewise, we did not find a direct relationship between body mass and prolactin levels in incubating female eiders, because the birds seldom reach a phase III during normal incubation (Criscuolo et al, 2001). Such a result is consistent with the incubation strategy of capital incubators, which because they depend almost exclusively on their endogenous nutrient reserves are able to lose a large amount of body mass without threatening their reproduction or survival (Cherel et al, 1988;Moreno, 1989). On the other hand, a deteriorated adult body condition at hatching could have an impact on the posthatch parental behavior.…”
Section: Mass Loss Prolactin Levels At Hatching and Posthatch Parensupporting
confidence: 81%
“…Phase II corresponds to a long period of economy, during which the rate of body mass loss and the body protein utilization are low, most of the energy being derived from lipids. Phase III is critical because both rates of body mass loss and protein utilization are increasing while body lipids neared depletion (Cherel et al, 1988).…”
Section: Effect Of Eggs and Nest On Prolactin Levelsmentioning
confidence: 99%
“…For example, in a study of 10 passerine species caught in the spring on an Italian island just after a migratory flight of at least 500 km from North Africa, only individuals with depleted fat stores and critically emaciated breast muscles (an important source of protein) showed high corticosterone levels (!45 ng/mL; Jenni et al 2000)-levels that were suggested to be associated with increased protein breakdown, as in voluntarily fasting king penguins (Aptenodytes patagonica; Cherel et al 1988). Red knots are usually thought to arrive on the breeding grounds with some fuel (fat and protein) stores remaining (Davidson and Evans 1988;Davidson and Morrison 1992).…”
Section: High Baseline Levels Of Corticosterone At Arrival On the Brementioning
confidence: 99%
“…However, this does not seem to apply for seasonal fattening species like the garden warbler, which show no corticosterone increase while drawing on lipid reserves (Cherel et al 1988, Schwabl et al 1991.…”
Section: Discussionmentioning
confidence: 99%